Probability Distribution Function of the Electric Field Strength From a CW IEMI Source - Glazunov, Andres Alayon; Backstrom, Mats; Oakes, Benjamin Donald (IEEE transactions on electromagnetic compatibility, 2014)
A statistical method for predicting the vulnerability of a target, i.e., critical equipment, located inside a building subject to a radiated Intentional Electromagnetic Interference (IEMI) source outside a building, has been devised. Combining probability density functions of small- and large-scale fluctuations of the electric field strength results in a Suzuki distributed electric field strength impinging at the equipment. Specifying the susceptibility level or the critical electric field strength of the target, the vulnerability of a target is evaluated as a function of the distance between source and target, taking into account losses from in and outside the building. Vulnerability isocontours defined as lines of constant probability of exceeding the susceptibility level are presented for a generic, continuous wave power source in a scenario emulating a dense urban microcell propagation environment. A comparison of the vulnerabilities predicted based on the Suzuki and the Lognormal distributions are also been provided for the same scenario. The proposed method provides estimates of critical distances of radiated IEMI attacks and may have use when deciding on the perimeter defense of a facility.